Polarization rotation associated with phonon dynamics in monoclinic C phase near morphotropic phase boundary studied by diffuse and inelastic X-ray scattering from a Ti-composition-gradient Pb[(Mg1/3Nb2/3)1–xTix]O3 single crystal. (18th August 2018) - Ohwada, K.; Tsukada, S.; Matsuura, M.; Tsutsui, S.; Baron, A. Q. R.; Mizuki, J.; Namikawa, K.
ABSTRACT: We have investigated polarization rotation associated with phonon dynamics in the relaxor ferroelectrics Pb[(Mg1/3 Nb2/3 )1– x Ti x ]O3 . The intensity distributions of the diffuse scattering patterns show intensity- crossover behavior in the monoclinic- C ( MC ) phase over a wide Ti composition range (29 < x < 32 mol%). The transverse acoustic (TA) mode of the crossover region along the [001] direction softens and is damped, strongly correlating with the central peak intensity, which originates in the polar regions. These results indicate that the lattice can easily deform in the MC phase, and the polarization can rotate easily by associating with the TA mode.